Comparison study of agricultural waste for composite material - Abdullah, Anuar; Omar, Mohamad Fakhrul Zaman; B., Mohd Hannan; Mohd Nor Munawar, Nur Sofeana Zulaika (Penerbit MARDI, 2018)
The potential of natural fiber as raw material in the manufacturing of composite material is highly recommended. Lot of natural resources are wasted by just burning of agricultural residue. This study is an attempt to evaluate the possibility of producing composite material from a mixture of long kenaf fiber mixed with coconut fiber, loofah and fiber glass with the aid of a binder called epoxy. The mixing ratio of resin and natural fiber is 60:40, while for hardener to epoxy is 1:2. Long kenaf fiber was selected because of its strength compared to chopped kenaf. Tensile tests were conducted to measure its strength. The mechanical testing was done according to ASTM D 3039/D 3039M. The highest Young’s modulus obtained was from kenaf followed by kenaf and fiber glass, kenaf and coconut fiber and kenaf and loofah fiber with 9.2GPa, 9.1GPa, 6.2GPa and 6.0GPa respectively.